Mytravelbuddies – A sharing platform by travelers for travelers - Ahmad Dahlan, Abdul Rahman; Mohamad Saupe, Nor Akma; Mohamad, Nur'Aqilah; Ayub, Nuwailah (www.researchpublish.com, 2017)
This paper proposes a conceptual solution to help people plan their travelling smoothly by providing a variety of travel packages and useful information on travelling through a mobile application platform (MyTravelBuddies). MyTravelBuddies is a Consumer-to-Consumer (C2C) business model which aims to provide a platform for travel agencies to promote their travel packages to the customers as well as a One-Stop Center for the customers to find the best travel packages that suited their budget and travel plan. This system provides a platform for advertising travel package only, whereas the process of the transaction occurs outside this system. Nine blocks of Business Model Canvas (BMC) framework, Literature Review, strategy canvas, value proposition design canvas (VPC), environmental map and conducting interview/survey with potential customers to validate BMC/VPC have been used as the methodologies for this paper.